Engaging EFL Learners in Literature by Comparing Books to Their Film Adaptations in Higher Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article investigates an innovative technique of the recent approach Teaching English through literature that is titled teaching English through literature in higher education by comparing books to their film adaptations where students are not only involved in learning literature, but also can enhance their language skills and systems.